Preparation of bioactive polymer-based composite by different techniques and application in tissue engineering: A review - Azad Alam, Mohammad; Asoushe, Mohammad Hamed; Pourhakkak, Pouran; Gritsch, Lukas; Alipour, Alireza; Mohammadi, Somaye (Journal of Composites and Compounds, 2021)
Tissue engineering (TE) employs biological, chemical, and engineering methods to regenerate and restore injured or lost living tissues by applying biologically activated biomaterials, cells, and molecules. The fast and convenient restoration of tissue is a great challenge, emphasizing the need to imitate tissue structure and its physicochemical, biological, and mechanical behavior to give back the desired functionality of damaged tissue. Depending on the particular tissue, numerous requirements have to be fulfilled with the help of material and scaffold design that provides a base for cell adhesion and proliferation. As a result, countless biodegradable and bioresorbable materials have been extensively examined. Composite systems combine the benefits of bioactive ceramics and polymers, which seem to be good alternatives for bone tissue engineering. This article intends to introduce bioactive polymer, tissue engineering methods, the kinds of biomaterials applied in scaffold invention, and the different approaches to producing the bioactive polymer-based composites with various structures such as porous, membrane, and 3D structure. Biomaterials and invention techniques could crucially influence the consequences of the scaffold's design architectures, cell proliferation, and mechanical behavior. Moreover, an excellent scaffold assists cell generation and the provision of cell nutrients in the human body with their particular material characteristics.